THE EFL STUDENT TEACHERS' DEBATE PRACTICE: PROBLEMS AND SOLUTIONS - Ayu Puji Astuti; Fitri Budi Suryani; Diah Kurniati (Universitas Muria Kudus, 2022)
Debate is considered as one of the best ways and interesting classroom activity of speaking practice. It is also one of the most challenging practices among the others. Furthermore, debate in the foreign language classroom generally helps English learners to develop their communicative abilities. Nevertheless, some English learners’ still have problems in doing debate. This study aims to explore the EFL student teachers’ problems and strategies to solve those problems in debate practicing in academic speaking class at Universitas Muria Kudus. This study is a qualitative research with the questionnaire and interview as the instruments of collecting data. The result of this study shows that there were eleven problems faced by the EFL student teachers in debate practicing in academic speaking class. Meanwhile, the students implement seven strategies to solve those problems. This study suggests that lecturers know the potential problems in debate practicing to anticipate the difficulties when teaching debate as well as to inform the students about the strategies to cope with the problems in debate practicing.